Structure of the native pyruvate dehydrogenase complex reveals the mechanism of substrate insertion - Jana Škerlová (Nature Portfolio, 2021)
The pyruvate dehydrogenase complex (PDHc) is a large multienzyme complex that converts pyruvate into acetyl-coenzyme A and in E. coli the core of the PDHc is formed by 24 copies of dihydrolipoyl transacetylase. Here, the authors present the cryo-EM structure of the E. coli dihydrolipoyl transacetylase 24-mer core in a native resting state including lipoyl domains, and discuss the mechanism of substrate shuttling by the lipoyl domains.